ANN-Based Binary Backtracking Search Algorithm for VPP Optimal Scheduling and Cost-Effective Evaluation - Hannan M.A.; Abdolrasol M.G.; Mohamed R.; Al-Shetwi A.; Ker P.; Begum R.; Muttaqi K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cost effectiveness; Cost reduction; Electric power transmission networks; Learning algorithms; Neural networks; Renewable energy resources; Scheduling; Wind; Backtracking search algorithms; Charging/discharging; Correlation coefficient; Mean absolute error; Optimal scheduling; Optimization algorithms; Renewable energy source; Virtual power plants (VPP); Electric power system control